Retrospective Case Series of 376 Hanging Suicides in Bangladesh : Epidemiological and Forensic Perspectives - Rony, Md Shyful Islam; Islam, Samia Afsana; Karim, Md Fazlul; Sultana, Sharmin; Afroze, Nusrat; Ahmed, Tasnuva (Journal of Brahmanbaria Medical College, 2026)
Background: Suicide means self destruction. One can takes up any method to cause harm to himself. In Bangladesh there are different methods like ingestion of poison, hanging, drug overdose and in other countries most prevailing methods are gunshot. Suicide by hanging is common in Bangladesh. This study was done to identify the socio economic factors, other associated factors and post mortem examination finding of hanging cases. Material and Methods: This retrospective study was conducted among victims of hanging brought to Dhaka Medical College morgue during the period January 2015 to December 2015. Various identification data of the victim like age, sex, marital status, permanent address, suspension of dead body along with places of incidence, time and suspected causes of death were noted from the inquest report accompanying the dead bodies. Results: A total 376 cases of hanging was examined. Maximum no. of cases were within the age limit of 21- 30(36%) there were male predominance 208(55.32%) associated features of hanging we found maximum due to family disputes 110(29.3%) most of them used soft material as ligature material 245(64.6%). Conclusion: The high incidence of hanging in young male adults impose a serious effect in our economy. Journal of Brahmanbaria Med. Coll. Volume 07 Issue 01 Jan 2025 ; 8-10